Peranan Religiositas Islam terhadap Kesejahteraan Psikologis: Sebuah Pendekatan Kajian Literatur Sistematis - Siska Praditya; Hani Fadilah Humaira; Fath Yustia Hendrawan; Fuad Nashori (Psychopolytan : Jurnal Psikologi, 2025)
The objective of this study is to examine the influence of Islamic religiosity on psychological well-being and to identify the most influential dimensions of religiosity. The research employed a systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, drawing literature from Google Scholar, Scopus, and Garuda. Inclusion criteria comprised quantitative and qualitative studies addressing Islamic religiosity and psychological well-being, published between 2020 and 2025, in journal articles or conference proceedings written in either Indonesian or English. The search keywords included “Islamic religiosity,” “religiusitas Islam,” “psychological well-being,” and “kesejahteraan psikologis.” A synthesis of 11 selected articles revealed that Islamic religiosity positively influences individuals’ psychological well-being across diverse populations. Individuals with higher levels of religiosity tend to demonstrate greater psychological well-being compared to those with lower levels. Specific dimensions of religiosity such as religious commitment, ritual experience, and worship practices contribute to psychological well-being through self-acceptance, life purpose, and positive relationships with others. These findings underscore Islamic religiosity as a critical factor in fostering psychological well-being.